Teacher Perceptions on Issues of Multigrade Teaching - Sangai, Sandhya; Choudhary, Megha (THE PRIMARY TEACHER, 2016)
Multigrade teaching refers to teaching different grades in the same classroom setting. It is not unique to India but is common in many developed and developing countries across the world. Sometimes, multigrade teaching is seen as a pedagogic tool that can assist in times of teacher shortage, budget constraints, etc. In many countries, multigrade teaching is practised in schools mostly situated in rural and sparsely populated areas. The provision of education in multigrade schools is limited by a number of challenges, which negatively affect the quality of teaching and learning. Many teachers feel that multigrade teaching is more demanding and complex than mono-grade teaching. Teachers, teaching in these schools, have only been trained in mono-grade pedagogy, and therefore, lack the knowledge and skills to effectively deal with multigrade classes. In order to improve the quality of education in multigrade schools, teachers need to be imparted training in multigrade teaching